Using lifestyle interventions and the gut microbiota to improve PTSD symptoms - Sugden, Steven G.; Merlo, Gia (Frontiers in Neuroscience, 2024)
Posttraumatic stress disorder is part of a spectrum of psychological symptoms that are frequently linked with a single defining traumatic experience. Symptoms can vary over the lifespan in intensity based on additional life stressors, individual stability, and connectedness to purpose. Historically, treatment has centered on psychotropic agents and individual and group therapy to increase the individual’s window of tolerance, improve emotional dysregulation, and strengthen relationships. Unfortunately, there is a growing segment of individuals with posttraumatic stress disorder who do not respond to these traditional treatments, perhaps because they do not address the multidirectional relationships between chronic cortisol, changes in the brain gut microbiota system, neuroinflammation, and posttraumatic symptoms. We will review the literature and explain how trauma impacts the neuroendocrine and neuroimmunology within the brain, how these processes influence the brain gut microbiota system, and provide a mechanism for the development of posttraumatic stress disorder symptoms. Finally, we will show how the lifestyle psychiatry model provides symptom amelioration.